Chondroitin sulphate reduces both cartilage volume loss and bone marrow lesions in knee osteoarthritis patients starting as early as 6 months after initiation of therapy: a randomised, double-blind, placebo-controlled pilot study using MRI. Issue 6 (1st March 2011) - Wildi, Lukas Martin; Raynauld, Jean-Pierre; Martel-Pelletier, Johanne; Beaulieu, André; Bessette, Louis; Morin, Frédéric; Abram, François; Dorais, Marc; Pelletier, Jean-Pierre
Abstract : Objective: To determine the effect of chondroitin sulphate (CS) treatment on cartilage volume loss, subchondral bone marrow lesions (BML), synovitis and disease symptoms in patients with knee osteoarthritis (OA). Methods: In this pilot multicentre, randomised, double-blind, controlled trial in primary knee OA, 69 patients with clinical signs of synovitis were randomised to receive CS 800 mg or placebo once daily for 6 months followed by an open-label phase of 6 months in which patients in both groups received CS 800 mg once daily. Cartilage volume and BML were assessed by MRI at baseline and at 6 and 12 months; synovial membrane thickness was assessed at baseline and at 6 months. Results: The CS group showed significantly less cartilage volume loss than the placebo group as early as 6 months for the global knee (p=0.030), lateral compartment (p=0.015) and tibial plateaus (p=0.002), with significance persisting at 12 months. Significantly lower BML scores were found for the CS group at 12 months in the lateral compartment (p=0.035) and the lateral femoral condyle (p=0.044). Disease symptoms were similar between the two groups. Conclusion: CS treatment significantly reduced the cartilage volume loss in knee OA starting at 6 months of treatment, and BML at 12 months. These findings suggest a joint structure protective effect of CS and provide new in vivo information on its mode of action in knee OA.